Nature of tackles that result in injury in professional rugby league - King, D.; Hume, P. A.; Clark, T. (Research in Sports Medicine, 2012)
A total of 31,655 tackles in 48 professional rugby league matches were coded from video for height and direction of tackle on the ball carrier. Injuries were recorded by team medical staff for injury date, time, site, type, mechanism, severity, and player position. Tackle-related injuries were most frequently the result of two tacklers being involved in tackling the ball carrier from the side at shoulder or midtorso body levels. The ball carrier had a higher injury rate when tackled from behind his visual field at shoulder height and in the fourth quarter of matches. Tacklers had a higher risk of injury when tackling from the side of the ball carrier, as the first tackler, and in the third quarter of matches. Coaches should focus on practicing correct technique during tackling with two or more tacklers and when tackling in the ball carrier's blind vision area.